Contamination status and risk assessment of fifteen elements in peanuts: a case study of Shandong Province, China - Dong, Fengguang; Feng, Xueying; Huo, Yapeng; Ni, Tieying; Xiao, Peirui; Gong, Chunbo; Chen, Youxia; Zhang, Yiyi; Yin, Shizhen; Wang, Guiqiang (Food Science and Technology, 2023)
Food safety has always attracted considerable attention in China. However, few studies have investigated the pollution, dietary exposure, and health risk assessment of fifteen elements in peanuts. Herein, we collected 620 samples from 16 districts in Shandong province from 2020 to 2021 and detected the concentrations of Mn, Cu, Li, Al, Ni, Ba, Cr, Cd, Se, Pb, Sn, V, As, Sb，and Hg. Further, we evaluated the contamination degree of elements in peanuts using the Single Factor Pollution Index, Nemerow Comprehensive Pollution Index methods, Pollutant Sharing Rate and Quality Grading Standards. Finally, we successful assessed the dietary exposure and health risk of thirteen elements using Target Hazard Quotient method based on the contents and peanut intake of Shandong residents. SPIM and NPIM results showed that the products were slightly polluted by Cu and Pb. THQ results showed that dietary exposure risk of children was two to three times than that of adults, suggesting that children were more susceptible to non-carcinogenic risk from metals. HI results indicated that excessive peanut intake would harm human health, especially to children. Higher dietary exposure risk existed in Cu, Ni and Mn.